Electronic structure of materials : challenges and developments - Chezhina, Natalia; Korolev, Dmitry (Singapore : Pan Stanford Publishing, 2019)
This book is a short survey of magnetochemistry as a promising method for revealing the electronic structure of inorganic substances, particularly solid oxide materials. It is supported by five chapters that describe materials with various structures and applications, showing how the method of magnetic dilution with the aid of other physical methods (electron spin resonance, magnetization, Raman and Mössbauer spectroscopy, and electrical conductivity), accompanied by thorough structural and quantum mechanical studies, may be used for describing the states of atoms and interatomic interactions in multicomponent oxide systems. The book will serve as a guide for researchers in the field of various oxide materials, since it shows the roots for selecting the best structures and qualitative and quantitative compositions of oxide materials on the basis of the knowledge about their electronic structure. It is devoted to some of the most popular structures of multicomponent oxides among modern materials--perovskites and pyrochlores--giving a unified approach to their chemical structure.
Fundamentals of Magnetochemistry Natalia V. Chezhina and Dmitry A. Korolev Phase Composition and Magnetic Characteristics of Solid Solutions and Complex Oxides Based on Scandium Molybdate Sc2-2xGd2xMo3O12 (0 < x < 1) Dmitry A. Korolev and Mariia D. Sapova Problems of Electron Structure of Colossal Magnetoresistors Anna V. Fedorova and Natalia V. Chezhina Influence of the Nature of Dia- and Paramagnetic Elements on Electron Structure and Electrophysical Properties of Doped Lanthanum Gallate Dmitry A. Korolev and Natalia V. Chezhina Magnetic Behavior of Multicomponent Bismuth Niobates and Bismuth Titanates, with Pyrochlore and Layered Perovskite Structure Irina V. Piir et al.
"Jenny Stanford Publishing"
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Chemistry / General; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Nanostructures; Electronic structure; Materials -- Electric properties; Electronic apparatus and appliances -- Materials